Exploring EFL learners' writing errors The Case of Second Year EFL Students at the University of Souk-Ahras - KHELIFA Yousra (My University, 2023)
Abstract The current study aims at figuring out and analyzing the various types of errors made by second year EFL learners in writing at the Department of English at the University of Souk-Ahras, and exploring the major causes that stand behind committing such errors. To examine the main hypothesis that suggests that spelling, grammar mistakes and word choice are the types of errors that learners make the most while writing in EFL, and that learners’ incomplete knowledge of the target language, and the wrong application of the rules are the main causes for making written errors, an analysis of fourteen (14) students’ written essays was done. In addition, a students’ questionnaire was designed and distributed to the sample of the study which is 33 second year EFL learners from the total number of 107 learners at the Department of English, in order to know the main causes behind making errors in EFL writing. The findings confirm that second years students make different types of written errors which include: capitalization, spelling, word choice, punctuation errors, verb tense, wrong word form, unclear ideas, errors of articles, miss-ordering of ideas and errors of singular/plural. Moreover, the findings brought from students’ questionnaire reveal that the highest frequencies of causes stand behind committing errors in writing are the lack of grammatical rules and the limited time for completing a written task inside the classrooms. The present study aims to provide evidence for EFL teachers about the common errors that EFL learners make and the reasons that stand behind committing them. Thus, much more attention would be paid to the selection and application of effective methods and techniques to improve EFL learners’ writing skills. Our study aims also to raise learners’ awareness about their frequent errors in writing, so that they will take it seriously and try their best to strengthen their writing skills. --------------------------- الملخص تهدف الدراسة الحالية إلى إبراز و تحليل أنواع الأخطاء المرتكبة من قبل متعلمي اللغة الانجليزية كلغة أجنبية بقسم اللغة الانجليزية لجامعة سوق أهراس، كما أنها تهدف للكشف عن الأسباب الرئيسية خلف ارتكاب مثل هذه الأخطاء. لفحص الفرضية الأساسية التي تقترح أن التهجئة والأخطاء النحوية و اختيار الكلمات هم أنواع الأخطاء التي يرتكبها المتعلمين بكثرة أثناء الكتابة باللغة الانجليزية كلغة أجنبية، وان المعرفة الغير مكتملة للطلاب للغة الهدف و التطبيق الخاطئ للقواعد هي الأسباب الأساسية لارتكاب الأخطاء الكتابية، تم تحليل أربعة عشر (14) مقالة مكتوبة من قبل طلاب السنة الثانية ليسانس بقسم اللغة الانجليزية ، بالإضافة إلى استخدام استبيان للطلاب الذي صمم و وزع على عينة متكونة من 33 طالبا في السنة الثانية بقسم اللغة الانجليزية من العدد الإجمالي (107 طالبا) لمعرفة الأسباب الأساسية خلف ارتكاب الأخطاء الكتابية باللغة الانجليزية كلغة أجنبية. أثبتت النتائج أن طلاب السنة الثانية يرتكبون أنواعا مختلفة من الأخطاء الكتابية التي تتضمن الكتابة بالأحرف الكبيرة، التهجئة، اختيار الكلمات، أخطاء علامات الوقف، ازمنة الفعل، كتابة الكلمات ، أفكار غير واضحة، أخطاء التعريف و التنكير، عدم ترتيب الأفكار وأخطاء صيغة المفرد و الجمع. علاوة على ذلك، كشفت نتائج استبيان الطلاب أن الأرقام الأعلى لأسباب ارتكاب الأخطاء في الكتابة هي افتقار القواعد النحوية إلى جانب الوقت المحدود لإنهاء النشاط الكتابي داخل الأقسام .نأمل من خلال هده الدراسة تقديم شواهد لمدرسي اللغة الانجليزية كلغة اجنبية حول الاخطاء الكتابية الشائعة لدى متعلمي اللغة الانجليزية كلغة اجنبية و الاسباب الكامنة وراء دلك،. مما قد يؤدي الى ايلاء المزيد من الاهتمام باختيار الاساليب و التقنيات الفعالة لتطوير مهارات الكتابة لدى المتعلمين. كما تهدف الدراسة ايضا الى زيادة الوعي لدى متعلمي اللغة الانجليزية كلغة اجنبية حول أخطاءهم المتكررة في الكتابة، بحيث ياخدون الامر على محمل الجد و يبدلون قصارى جهدهم لتعزيز مهاراتهم في الكتابة. --------------------------- Resumè La prèsente ètude vise à dèterminer et à analyser les diffèrents types d’erreurs commises par les apprenants EFL de deuxième annèe à l’ècrit au dèpartement d’anglais de l’Universitè Souk-Ahras, et à explorer les principales causes qui les sous-tandent de telles erreurs. Examiner l’hypothèse principale qui suggère que l’orthographe, les fautes de grammaire, et le choix des mots sont les types d’erreurs que les apprenants commettent le plus lorsqu’ils ècrivent en EFL, et que la connaissance incomplète des apprenants de la langue cible et la mauvaise application des règles sont les principales causes d’erreurs ècrites, une analyses des dissertations ècrites de quatorze (14) ètudiants a ètè effectuèe. De plus, un questionnaire destinè aux ètudiants a ètè conçu et distribuè à l’èchantillon de l’ètude qui est de 33 apprenants EFL de deuxième annèe sur le nombre total de 107 apprenants du Dèpartement d’anglais, afin de connaitre les principales causes des erreurs d’ècriture EFL. Les rèsultats confirment que les ètudiants de deuxième annèe commettent diffèrents types d’erreurs ècrites, notamment : la capitalisation, l’orthographe, le choix des mots, les erreurs de ponctuation, le temps verbal, la mauvaise forme des mots, les idèes peu claires, les erreurs d’articles, le mauvais ordre des idèes et les erreurs de singulier/ pluriel. De plus, les rèsultats tirès du questionnaire des ètudiants rèvèlent que les causes les plus frèquantes des erreurs d’ècriture sont le manque de règles grammaticales et le temps limitè pour effectuer une tàche ècrite dans les salles de classe. La prèsente ètude vise à fournir aux enseignants d’EFL des preuves des erreurs courantes commises par les apprenants d’EFL et des raisons qui les motivent. Ainsi, une attention beaucoup plus grande serait accordèe à la sèlection et à l’application de mèthodes et de techniques efficaces pour amèliorer les compètences en ècriture des apprenants EFL. Notre ètude vise ègalement à sensibiliser les apprenants à leurs frèquentes erreurs d’ècriture, afin qu’ils les prennent au sèrieux et fassent de leur mieux pour renforcer leurs compètences en ècritures.